Efficiency and challenges in public real estate management: insights from Lithuania - Cohen, Viktorija; Bereznauskė, Evelina; Burinskas, Arūnas; Raslanas, Saulius (International Journal of Strategic Property Management, 2023)
Public real estate is considered an integral part of national wealth. It generates a wide range of economic activities that contribute to creating and providing common public goods. This study examines the efficiency of public real estate management in Lithuania. Our findings show that public property use, disposal, and management strongly depend on the managerial approach. We apply data envelopment analysis (DEA) in addition to the income value, regression, and correlation methods. We find that there are certain biases present due to the exclusion of some state-owned properties from the public register. Furthermore, we identify the need for greater precision in the indicators used for financial reporting of state-owned assets. The excessive number of vacant asset units poses a challenge, as it requires substantial maintenance expenditures. Moreover, the appraisal of alternative use of these assets is lacking, thereby limiting the potential for maximizing public benefits. Our analysis reveals that the rental price per 1 m2 and the residual value of the leased premises are the most critical determinants influencing the management efficiency of publicly owned property. Furthermore, it is evident that the residential property is the only type of state-owned property managed efficiently within the Lithuanian public sector. These findings underscore the importance of formation of robust public real estate policies.